Prospective Observational Study of High-Dose Carbon-Ion Radiotherapy for Pelvic Recurrence of Rectal Cancer (GUNMA 0801) - Shiba, Shintaro; Okamoto, Masahiko; Kiyohara, Hiroki; Ohno, Tatsuya; Kaminuma, Takuya; Asao, Takayuki; Ojima, Hitoshi; Shirabe, Ken; Kuwano, Hiroyuki; Nakano, Takashi (Frontiers in Oncology, 2019)
Background and purpose Favorable clinical outcomes of carbon-ion radiotherapy for pelvic recurrence of rectal cancer have been described by previous prospective phase I/II and II studies; however, these studies were performed at a single institution. Therefore, we conducted a prospective observational study aimed at exploring whether carbon-ion radiotherapy for post-operative pelvic recurrence of rectal cancer provides a less invasive local treatment strategy with higher cure rates than other anticancer treatments. Materials and methods Patients 1) with pelvic recurrence of rectal cancer, as confirmed by histology or diagnostic imaging; 2) without distant metastasis; 3) who had undergone curative resection of their primary disease and regional lymph nodes, without gross or microscopic residual disease; and 4) with radiographically measurable tumors were included in this study. The total carbon-ion radiotherapy dose for all patients was 73.6 Gy (relative biological effectiveness) administered in 16 fractions once daily for 4 days a week (Tuesday to Friday). Results A total of 28 patients were enrolled between October 2011 and July 2017. The median follow-up duration was 38.9 months. The 3-year overall survival, local control, and progression-free survival rates were 92%, 86%, and 31%, respectively. At the time of the analysis, 4 patients had local recurrence, and 7 had died of rectal cancer. None of the patients developed grade 3 or higher acute toxicities. Late toxicities occurred in 2 and 7 patients who developed grade 3 pelvic infection and grade 2 peripheral neuropathy, respectively. Conclusion Carbon-ion radiotherapy for pelvic recurrence of rectal cancer showed favorable clinical outcomes and is a highly curative and less invasive local treatment.